On the performance of X̄ control chart for known and unknown parameters supplemented with runs rules under different probability distributions - Mehmood, Rashid; Qazi, Miss Sara; Riaz, Muhammad (Journal of statistical computation and simulation, 2018)
In this study two design structures of control chart are proposed for known and unknown process parameters, under the variety of runs rules and process distributions. The proposed structures are developed by taking into account certain margin of enhancements and limitations in existing studies as the subjects of current article. Outcomes of the study are obtained through two most commonly used performance measures, generally known as false alarm rate and power curve. Based on these measures, conclusion of the study shows that proposed structures perform outstandingly as compared to various existing counterparts. In continuation to, design structure for unknown parameters has capability to overcome the issue of existing runs rules, which generally occur when parameters are unknown.